Regulation of in vivo transcription of the Escherichia coli K-12 metJBLF gene cluster. - Kirby, T W (1986)
We subcloned DNA of the intercistronic region between the divergently transcribed metJ and metB genes of Escherichia coli into the transcription-fusion vector pK01 and localized the metJ promoters by deletion analysis. The plasmid-borne promoters of both genes were repressed by chromosomal metJ. In addition, S1 nuclease mapping of chromosomally derived mRNA from a derepressed strain revealed the start sites of transcription for metBL, metF, and metJ. The metBL and metF genes each had a single transcript which was repressed by metJ, while the metJ gene had three transcripts, of which the first was strongly repressed by metJ, the second was less strongly repressed, and the third was not repressed.